2020
DOI: 10.1101/2020.12.24.20248786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptable Performance of the Abbott ID NOW Among Symptomatic Individuals with Confirmed COVID-19

Abstract: INTRODUCTIONPoint of care diagnostic tests for SARS-CoV-2, such as the ID NOW, have great potential to help combat the COVID-19 pandemic. The ID NOW is approved by the United States Food and Drug Administration (FDA) for the detection of SARS-CoV-2 in symptomatic individuals within the first 7 days of symptom onset for COVID-19 if tested within 1 hour of specimen collection. However, clinical data on the performance of the ID NOW is limited, with many studies deviating from the manufacturer’s instructions and/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The assay has processing times as low as 5 min for positive results with high viral loads and 15 min for specimens with lower viral loads or negative results. Compared to LDTs or commercial NAATs, many recent studies have demonstrated an excellent specificity/negative percent agreement (NPA) near 100% but relatively poor sensitivity/positive percent agreement (PPA) of between 48% and 70% for the detection of SARS-CoV-2, while other studies showed a high specificity/NPA (∼100%) as well as high sensitivity/PPA values above 90% ( 290 , 301 , 341 347 ).…”
Section: Laboratory Methods For the Detection Of Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations
“…The assay has processing times as low as 5 min for positive results with high viral loads and 15 min for specimens with lower viral loads or negative results. Compared to LDTs or commercial NAATs, many recent studies have demonstrated an excellent specificity/negative percent agreement (NPA) near 100% but relatively poor sensitivity/positive percent agreement (PPA) of between 48% and 70% for the detection of SARS-CoV-2, while other studies showed a high specificity/NPA (∼100%) as well as high sensitivity/PPA values above 90% ( 290 , 301 , 341 347 ).…”
Section: Laboratory Methods For the Detection Of Sars-cov-2mentioning
confidence: 99%
“…The reasons for the disparities in sensitivity/PPA between studies are likely multifold and include differences in the patient population (setting, host factors, and the presence or not of compatible symptoms), the specimen type, the timing between collection and testing, the transport conditions used (dry swabs or transport media), the quality of specimens (prospective versus retrospective), the spectrum of viral loads in the specimens evaluated (proportion of specimens with low viral loads), or differences in performance characteristics of the comparator method(s) ( 290 , 301 , 341 347 ). For example, the swab type affected IDNCOV performance, where NP swabs showed a PPA of 64%, compared to 48% with nasal swabs ( 348 ).…”
Section: Laboratory Methods For the Detection Of Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients aged 14-100 (median age 63) recruited into the study were included irrespective of the reason for referral to the emergency department but showed symptoms associated with COVID-19 and / or a high epidemiological risk (Table 1) [3,13]. The evaluation of the collected findings within the scope of the study was carried out with the consent of the patients and completely anonymised.…”
Section: Clinical Cohorts Study Plan and Ethical Clearancementioning
confidence: 99%